Peran Al-Qur’an (Pengaruh Al-Qur’an dalam Membentuk Bahasa Arab dan Sastra) - Syarifuddin Ondeng; Andi Abdul Hamzah; Zulfiah Sam (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2024)
This research aims to determine the role of the Al-Qur'an and its influence in shaping Arabic language and literature. The Al-Qur'an has very high miracles, both at the level of content and the language it uses. The height of the language of the Qur'an can be seen in the aspects of phoneme selection, word selection, sentence selection and the effects they cause. This research uses qualitative research which focuses more on aspects of in-depth understanding, using library research methods. The research results found that: The influence of the Al-Qur'an in shaping Arabic language and literature is very large and profound. The language of the Koran is considered the pinnacle of beauty and excellence in the structure of the Arabic language and has made a significant contribution to the development of Arabic literature. The strength and beauty of the language of the Koran has become an inspiration and model for Arabic speakers in developing literary skills and their language, such as the beauty of the language, use of vocabulary and terms, rhetorical style, influence on Arabic poetry, as well as the role of the Al-Qur'an in providing inspiration and guidance for Arab writers and poets in creating literary works.